Cultura(s) nos sertões: impactos de políticas culturais em assentamentos rurais no Ceará - Cabral, Bruna Delfino (2018)
The creation of the Law 12.343/2010, which institutes the National Plan of Culture (Plano Nacional de Cultura - PNC) and the establishment of the National Policy for Living Culture (Política Nacional de Cultura Viva - Law 13.018/2014), provided an undeniable advance in the development of cultural policies in Brazil. In this context, this research aimed to analyze the cultural policies implemented in rural settlements, having as reference the Pontões and Pontos de Cultura (Big Points and Culture Points). The spatial scoping of this research is the group of three rural settlements located in the Sertões de Canindé Territory: Tiracanga, Todos os Santos and Santo Antônio. The first two belong to the municipality of Canindé and the third to the municipality of Caridade. For this study, the period analyzed was from 1989 to 2017. This is a qualitative research whose methodology was composed of four stages: bibliographical and cartographic survey; fieldwork; systematization and analysis of collected information and data; and elaboration of the final text. Cultural policies are transforming geographic space and, in this way, alter the forms/contents of space, interfering with the meanings and senses that this space acquires for individuals. Thus, the Big Point and the Culture Point implemented in the rural settlements affected the daily life of the settlers, causing positive transformations and contributing to their development. The Art and Culture Program in Agrarian Reform (Pacra) and the Technical Advisory and Extension Service (ATER) functioned as important mediators between the State and the settled peasants, collaborating significantly to the access to cultural policies. It was verified that these policies made possible the social inclusion, strengthening Culture as an expression of values and feelings, potentializing the Peasant Culture.